On the β-Dual of Banach-Space-Valued Difference Sequence Spaces - Bhardwaj, V.K.; Gupta, S. (Український математичний журнал, 2013)
The main object of the paper is to introduce Banach-space-valued difference sequence spaces `∞(X, ∆), c(X, ∆), and c₀(X, ∆) as a generalization of the well-known difference sequence spaces of Kizmaz. Основна мета статтi — ввести простори диференцiальних послiдовностей `∞(X, ∆), c(X, ∆), значення яких лежать у банаховому просторi, i c₀(X, ∆), як узагальнення добре вiдомих просторiв диференцiальних послiдовностей Кiзмаза.